Traveling Wave Solutions of Some Coupled Nonlinear Evolution Equations. (20th May 2013) - Khan, Kamruzzaman; Akbar, M. Ali
Abstract : The modified simple equation (MSE) method is executed to find the traveling wave solutions for the coupled Konno-Oono equations and the variant Boussinesq equations. The efficiency of this method for finding exact solutions and traveling wave solutions has been demonstrated. It has been shown that the proposed method is direct, effective, and can be used for many other nonlinear evolution equations (NLEEs) in mathematical physics. Moreover, this procedure reduces the large volume of calculations.